Vaccination against H5 HP avian influenza virus leads to persistent immune response in wild king penguins - Lejeune, Mathilde; Tornos, Jérémy; Bralet, Tristan; De Pasquale, Camille; Marçon, Elsa; Massin, Pascale; Grasland, Béatrice; Stier, Antoine; Boulinier, Thierry (Springer Nature, 2026)
Since 2021, the panzootic nature of high pathogenicity avian influenza (HPAI) represents an increasing threat to wild vertebrate populations. In this context, recent vaccines developed for poultry could provide tools for the conservation of wild endangered birds populations. The king penguin (Aptenodytes patagonicus), a long-lived seabird breeding in dense colonies with an extended chick-rearing period, has been identified as a possible surrogate species for a vaccination trial in a sub-Antarctic natural setting. Here we investigate the immune response of king penguin chicks to a self-amplifying mRNA vaccine against a H5 HPAI clade 2.3.4.4b protein. The cohort entails thirty vaccinated chicks (primo- and boost-injections), and 20 unvaccinated controls. Along 250 days of monitoring, the vaccinated chicks show a high and persistent immune response, granting a strong sero-neutralisation capacity against the virus, up to fledging. No adverse effects are observed. Screening for antibodies against unspecific avian influenza viruses suggests that no natural infection has occurred over the entire trial. The emergence of HPAI in the Southern Indian Ocean in October 2024 highlights the timeliness of such experimental tests. Our results thus show the vaccine could provide a potentially powerful tool for mitigation of avian flu outbreaks in the wild.